Teori Etologi dan Ekologi Perkembangan Perspektif Psikologi Islam - Muhammad Luthfi Mahendra (Amorti: Jurnal Studi Islam Interdisipliner, 2023)
Psychology is a branch of science that deals with human behavior. In psychology there is one study that discusses development. Developmental psychology is a psychological study that discusses individual development, from the factors that influence it to how it develops. In this study, there are several theories that discuss the things that affect individual development. One of the theories in developmental psychology is contextual theory which includes ethology and ecology theory. This study seeks to discuss in depth the two contextual theories. The method used in this research is descriptive qualitative method, as well as data collection taken from books, journal documents, or other documents because they are included in library research. Ethological theory argues that individual development is influenced by attachments that occur at the beginning of an individual's life, while in ecologic theory, individual development is determined by the environment in which the individual lives.